DOI: 10.14264/uql.2014.614
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and combustion enhancement in a Mach 12 shape-transitioning scramjet engine

Abstract: are to investigate and characterize the flow physics behind the Mach 12 REST engine's current performance, and then attempt to improve its combustion performance by tailoring the engine's fuel injection to its internal flow field without otherwise modifying the engine geometry. To meet these aims, the engine was studied both numerically and experimentally.The first-ever combusting simulations of a REST scramjet operating at Mach 12 conditions were performed for the Mach 12 REST engine using the CFD research co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(126 citation statements)
references
References 36 publications
(61 reference statements)
8
118
0
Order By: Relevance
“…As such, no further mention of the heat transfer gauges will be made, but further information is available in Ref. [32].…”
Section: B Experimental Methodologymentioning
confidence: 99%
“…As such, no further mention of the heat transfer gauges will be made, but further information is available in Ref. [32].…”
Section: B Experimental Methodologymentioning
confidence: 99%
“…The selected compression system is designed to decelerate the operating Mach 8 flow to Mach 2.5, where the boundary conditions used for the combustion chamber testing are based on the concept aircraft scramjet engine design (Table 2). High Mach number entry flow is investigated further in Reference [10] in recent research. The scramjet inlet was designed using methodology from studies carried out at Queensland University [11].…”
Section: Nozzle Expansionmentioning
confidence: 99%
“…The Mach 12 REST engine was considered for analysis, using initial conditions from [22] and geometry from [21]; the mixing efficiency curve was developed and used to describe the mass flow rate differential. The frictionless case was first compared to the case with friction losses; it was found that the inclusion of friction decreases combustion efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The initial combustor conditions, without fuel injection in the inlet of the engine, are = 0.1023 / , = 1560 , = 44.502 , = 3027 / and = 4.02 [22]. Though the real engine includes fuel injection in the inlet, and this changes the combustor inlet conditions, the case being considered here is without this fuel addition.…”
Section: Geometry and Mixing Profilementioning
confidence: 99%